Sex‐specific expression and DNA methylation in a species with extreme sexual dimorphism and paternal genome elimination. Issue 22 (12th March 2021) - Bain, Stevie A.; Marshall, Hollie; de la Filia, Andrés G.; Laetsch, Dominik R.; Husnik, Filip; Ross, Laura
Abstract: Phenotypic differences between sexes are often mediated by differential expression and alternative splicing of genes. However, the mechanisms that regulate these expression and splicing patterns remain poorly understood. The mealybug, Planococcus citri, displays extreme sexual dimorphism and exhibits an unusual instance of sex‐specific genomic imprinting, paternal genome elimination (PGE), in which the paternal chromosomes in males are highly condensed and eliminated from the sperm. Planococcus citri has no sex chromosomes and both sexual dimorphism and PGE are predicted to be under epigenetic control. We recently showed that P . citri females display a highly unusual DNA methylation profile for an insect species, with the presence of promoter methylation associated with lower levels of gene expression. Here, we therefore decided to explore genome‐wide differences in DNA methylation between male and female P . citri using whole‐genome bisulphite sequencing. We identified extreme differences in genome‐wide levels and patterns between the sexes. Males display overall higher levels of DNA methylation which manifest as more uniform low levels across the genome. Whereas females display more targeted high levels of methylation. We suggest these unique sex‐specific differences are due to chromosomal differences caused by PGE and may be linked to possible ploidy compensation. Using RNA‐Seq, we identify extensive sex‐specific gene expression and alternative splicing, but we find no correlation with cis ‐acting DNA methylation. Abstract : see also the Perspective by Peter Sarkies.